Hereditary Angioedema Type II: First Presentation in Adulthood with Recurrent Severe Abdominal Pain - Mohamed Abuzakouk; Nada AlMahmeed; Esat Memisoglu; Martine McManus; Aydamir Alrakawi (Case Reports in Immunology)
A 27-year-old Emirate man presented to Cleveland Clinic Abu Dhabi emergency department with a 4 year history of recurrent episodes of severe swellings affecting different parts of his body. He used to get 2 swelling episodes every week affecting either his face, hands, feet or scrotum and severe abdominal pain twice a week. Abdominal CT scan and a colonoscopy showed bowel wall oedema. There was no family history of similar complaint or of hereditary angioedema (HAE). Complement studies confirmed the diagnosis of HAE type II. He was commenced on danazol 100 mg twice daily and his symptoms resolved. This case report highlights the importance of considering HAE in patients with recurrent unexplained abdominal pain even in the absence of positive family history of HAE.